Evaluating electronic training programs in Jordanian universities in light of the Corona pandemic: a comparative study between public and private universities - Abdelrahman, Eman Jamil (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study aimed to evaluate the effectiveness of e-training programs in Jordanian universities during the COVID-19 pandemic, comparing public and private institutions. A descriptive-analytical approach was employed, utilizing both interviews and a questionnaire. The researcher developed a 20-item questionnaire and conducted interviews with faculty members to identify obstacles to e-training and suggest potential improvements. The study sample comprised 1,070 faculty members, with 765 from public universities and 305 from private universities. Additionally, intentional interviews were conducted with 50 faculty members. The results indicated that the overall effectiveness of e-training programs was rated as moderate, with no significant differences observed between public and private universities. The primary obstacle identified was insufficient funding for e-training, particularly during the pandemic. This study aims to assist university administrations in considering e-learning systems as effective alternative training methods. Furthermore, it seeks to explore new dimensions and skill sets for faculty members. Based on these findings, the research proposes strategies to enhance e-training, including improved budgeting and evaluation methods.